THE POSITION OF ISLAM NUSANTARA IN GEOPOLITICAL DINAMYCS OF ISLAMIC WORLD - Abdul Chalik (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2016)
Abstract: During the weakening of bargaining position of Islam in world’s view because of terrorism issue after the ‘Black September 2001’, ISIS arise, a socio-political organization that is even more extreme than the predecessor, al-Qaeda. ISIS not only make the West afraid because of all the exploitation, especially after the Paris terror in the mid of November 2015, but also hurt the feeling of Muslims as they involve the name of Islam-while the behavior is contrary to the belief in Islam. Geopolitically, the position of Islamic world is in dilemma; one side it must deal with the Muslims, while on the other side it should be in synergy with foreign powers against its own nation or brothers. The Islamic world position to face the power of ISIS is weak. Different from ISIS or al-Qaeda which is extreme and exclusive, Islam Nusantara is on the contrary. This article was written by a descriptive-explorative method by presenting the issues of the Islamic world today and its relationship with the ideology of Islam Nusantara being built.Abstrak: Peranan Islam Nusantara dalam Dinamika Geopolitik Dunia Islam. Tulisan ini berangkat dari kegelisahan terhadap lahirnya ISIS, sebuah gerakan sosial politik yang lebih ekstrim dibandingkan dengan pendahulunya, al-Qaeda. Satu sisi, organisasi ini tidak saja membuat Barat ketakutan atas segala sepak terjangnya, terutama pasca teror Paris di pertengahan Nopember 2015, pada sisi yang lain juga menciderai perasaan umat Islam karena dianggap mendompleng atas nama agama (Islam)—sementara perilakunya berlawanan dengan ajaran Islam. Secara geopolitik posisi dunia Islam mengalami dilema; satu sisi harus berhadapan dengan Muslim sendiri sementara pada sisi yang lain harus bersinergi dengan kekuatan asing untuk melawan bangsa atau saudara sendiri. Berbeda dengan Islam ala ISIS atau al-Qaeda yang bercorak ekstrim dan eksklusif, Islam Nusantara berpandangan sebaliknya. Artikel ini ditulis dengan metode ekploratif deskriptif—dengan menyajikan persoalan dunia Islam saat ini dan hubungannya dengan ideologi Islam Nusantara yang sedang dibangun.Keywords: Islam Nusantara, Islamic world geopolitics, ISIS